Development and characterization of 26 polymorphic microsatellite markers in Lateolabrax maculatus and cross-species amplification for the phylogenetically related taxa. (June 2016) - Zhang, Hao-Ran; Niu, Su-Fang; Wu, Ren-Xie; Zhai, Yun; Tian, Le-Tian
Abstract: The spotted sea bass Lateolabrax maculatus, a commercially important species of fishery resource in the Northwestern Pacific, has become a popular cultured fish species in China. Although the microsatellite markers of L. maculatus have been isolated, they mainly focused on dinucleotide-repeat loci. In this study, we developed 26 polynucleotide-repeat microsatellite loci for L. maculatus through high-throughput DNA sequencing technology. The number of alleles per locus ranged from 3 to 19. Observed and expected heterozygosities varied from 0.188 to 0.906 and 0.175 to 0.938, respectively. One locus showed significant deviation from Hardy-Weinberg equilibrium after Bonferroni correction. These 26 novel microsatellite markers will serve as useful tools which benefit population genetics studies and conservation management of L. maculatus . In addition, cross-species amplification tests showed that the transferability of 6 loci was positive across 10 species of two phylogenetically related families Latidae and Serranidae, and 3 loci were successful amplified in at least 5 species. The transferable loci would be helpful for the detection of genetic relationship and divergence between the tested taxa. Highlights: 26 new polynucleotide-repeat microsatellite loci were isolated in Lateolabrax maculatus. Transferability of 6 loci was positive across 10 phylogenetically related species of Latidae and Serranidae. These markers will help to study population genetics and conservation management.